Characterisation of cellular adhesion reinforcement by multiple bond force spectroscopy in alveolar epithelial cells. (23rd June 2017) - Nguyen, Ngoc‐Minh; Angely, Christelle; Andre Dias, Sofia; Planus, Emmanuelle; Filoche, Marcel; Pelle, Gabriel; Louis, Bruno; Isabey, Daniel
Abstract : Research article : To characterise the early phase of integrin‐mediated adhesion in alveolar epithelial cells, the force spectroscopy method is revisited by a new theoretical approach predicting adhesion reinforcement in multiple bonds working non‐cooperatively with homogeneous redistribution of the stretching force. The present results show that the multiple bond force spectroscopy method presently proposed enables detection of bond number and the impact of bond association on adhesion reinforcement. Abstract : Background Information: Integrin‐mediated adhesion is a key process by which cells physically connect with their environment, and express sensitivity and adaptation through mechanotransduction. A critical step of cell adhesion is the formation of the first bonds which individually generate weak contacts (∼tens pN) but can sustain thousand times higher forces (∼tens nN) when associated. Results: We propose an experimental validation by multiple bond force spectroscopy (MFS) of a stochastic model predicting adhesion reinforcement permitted by non‐cooperative, multiple bonds on which force is homogeneously distributed (called parallel bond configuration). To do so, spherical probes (diameter: 6.6 μm), specifically coated by RGD‐peptide to bind integrins, are used to statically indent and homogenously stretch the multiple bonds created for short contact times (2 s) between the bead and the surface of epithelial cells (A549). Using different separation speeds (v = 2, 5, 10 μm/s) and measuring cellular Young's modulus as well as the local stiffness preceding local rupture events, we obtain cell‐by‐cell the effective loading rates both at the global cell level and at the local level of individual constitutive bonds. Local rupture forces are in the range: f * = 60 − 115 pN, whereas global rupture (detachment) forces reach F * = 0.8 − 1.7 nN . Global and local rupture forces both exhibit linear dependencies with the effective loading rate, the slopes of these two linear relationships providing an estimate of the number of independent integrin bonds constituting the tested multiple bond structure (∼12). Conclusions: The MFS method enables to validate the reinforcement of integrin‐mediated adhesion induced by the multiple bond configuration in which force is homogeneously distributed amongst parallel bonds. Local rupture events observed in the course of a spectroscopy manoeuver (MFS) lead to rupture force values considered in the literature as single‐integrin bonds. Significance: Adhesion reinforcement permitted by the parallel multiple bond association is particularly challenging to verify for two reasons: first, it is difficult to control precisely the direction of forces experimentally, and second, because both global and local bond rupture forces depend on the effective loading rate applied to the bond. Here, we propose an integrin‐specific MFS method capable of detecting bond number and characterising bond configuration and its impact on adhesion strength.